2014
DOI: 10.1089/ars.2014.5874
|View full text |Cite
|
Sign up to set email alerts
|

Iron in Neurodegenerative Disorders of Protein Misfolding: A Case of Prion Disorders and Parkinson's Disease

Abstract: Improved understanding of the relationship between brain iron imbalance and protein aggregation is likely to help in the development of therapeutic strategies that can restore brain iron homeostasis and mitigate neurotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 185 publications
(205 reference statements)
0
27
0
Order By: Relevance
“…Copper [20] and iron [21] appear to be primarily responsible for toxicity via oxidative-stress-type mechanisms, since they can be reversibly oxidised and reduced [22]. Oxidised forms of iron and copper bind to αSyn and trigger conformational changes associated with the formation of the amyloid plaque [23]. Reduced forms of iron and copper ions (i.e.…”
Section: Role Of Heavy Metal Ionsmentioning
confidence: 99%
“…Copper [20] and iron [21] appear to be primarily responsible for toxicity via oxidative-stress-type mechanisms, since they can be reversibly oxidised and reduced [22]. Oxidised forms of iron and copper bind to αSyn and trigger conformational changes associated with the formation of the amyloid plaque [23]. Reduced forms of iron and copper ions (i.e.…”
Section: Role Of Heavy Metal Ionsmentioning
confidence: 99%
“…Despite these studies showing no changes in iron, there are others that suggest a strong role for PrP in iron metabolism [134]. An initial study suggested increases in both ferritin and iron response proteins in astrocytes in rodent scrapie models [135].…”
Section: Prion Diseasesmentioning
confidence: 99%
“…While considerable research has focused on copper, the relation of PrP to other metals remains patchy. The three metals that have gained some interest in this regard are zinc, manganese and iron (Brown, 2011;Singh et al, 2014;Watt and Hooper, 2003). This current investigation was inspired in part by a recent paper suggesting that PrP mediated increased zinc flux through AMPA receptors (Watt et al, 2012).…”
Section: Discussionmentioning
confidence: 99%